Aplikasi Level Biochar dan Jarak Tanam terhadap Pertumbuhan dan Produksi Rumput Raja (Pennisetum purpuphoides) - Adam H. L. Moruk; Oktovianus R. Nahak T. B. (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study is to obtain the level of biochar on the growth and production of king grass and the best planting distance on the growth and production of king grass and the interaction between the levels of biochar and the regulation of growth and production of king grass. The study was conducted in the experimental area of the Faculty of Agriculture, University of Timor, Sasi Village, South Bikomi District, North Central Timor Regency. The research lasted for 48 days or during 1 production period. Each production period lasts for 48 HST. The method used in this study is an experimental method, using a completely randomized design (CRD) factorial pattern of 3x3. The factors tested were the first factor in the biochar level and the second factor was the spacing and each combination of experiments was repeated 3 times. The variables observed in this study were plant height, number of tillers, number of leaves, leaf fresh weight and leaf dry weight. Data were analyzed by analysis of variance (Anova) according to the design used. Data analysis using SAS software version 9.1. The results showed that there was an interaction between the treatment of biochar doses and spacing to plant height growth of king grass, but for other variables there was no interaction. It was concluded that the level of biochar in increasing the growth of king grass varies, for plant height and number of tillers without using biochar can still grow optimally while for increasing the number of leaves at the level of use of 250 g / planting hole. Level 500 g / planting hole is effective in increasing the dry weight and fresh weight of king grass leaves. The best spacing on growth and production of king grass varies for plant height and the number of tillers the best spacing is 20 cm while for the most number of leaves increasing at a spacing of 40 cm. Plant spacing of 60 cm is effective in increasing the dry weight and fresh weight of king grass leaves as well as the interaction between biochar levels and plant spacing on plant height while on other variables there is no interaction.